2011
DOI: 10.1177/039463201102400221
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Laminin-1 Antibodies in Sera and Follicular Fluid of Women with Endometriosis Undergoing in Vitro Fertilization

Abstract: There is increasing evidence that autoimmune phenomena, including auto-antibody production, may affect fertility in women with endometriosis. The aims of this study are to evaluate anti-laminin-1 antibody (aLN-1) presence in sera and in follicular fluids (FF) of women with endometriosis undergoing IVF and its impact on oocyte maturation and IVF outcome. aLN-1 were measured by a home-made enzyme linked immunosorbent assay in sera and FF obtained from 35 infertile women with endometriosis and in sera from 50 fer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 32 publications
1
7
0
Order By: Relevance
“…18,19 Recently, we analyzed aLN-1 presence in the serum and FF of infertile women with endometriosis undergoing IVF. 20 Our data confirmed that aLN-1 levels were significantly higher in women with endometriosis when compared with infertile women without endometriosis. Interestingly, in the same study, we demonstrated a negative correlation between aLN-1 levels detected in FF and the number of metaphase II (MII) oocytes, suggesting that aLN-1 could affect oocyte maturation.…”
Section: Introductionsupporting
confidence: 84%
“…18,19 Recently, we analyzed aLN-1 presence in the serum and FF of infertile women with endometriosis undergoing IVF. 20 Our data confirmed that aLN-1 levels were significantly higher in women with endometriosis when compared with infertile women without endometriosis. Interestingly, in the same study, we demonstrated a negative correlation between aLN-1 levels detected in FF and the number of metaphase II (MII) oocytes, suggesting that aLN-1 could affect oocyte maturation.…”
Section: Introductionsupporting
confidence: 84%
“…Nine studies were identified affecting the reproductive system and possibly altering the possibilities for a successful IVF cycle [82,83,84,85,86,87,88,89,90]. Four of the aforementioned studies concerned ASA [87,89,90,91], 3 AEA [83,86,88], one AGA [82] and one aLN1 in the follicular fluid of women with endometriosis [85]. Although ALN1 is not classified as a reproductive-specific antibody, the study population is diagnosed with endometriosis, a conditioned that has been associated to aLN1 [92].…”
Section: Auto-antibodies Specifically Affecting the Reproductive Smentioning
confidence: 99%
“…This case report validates the approach of ART for infertile patients with AGA. The impact of aLN1 in follicular fluids was explored in a prospective cohort study [85]. Women positive for aLN1 presented with similar ongoing pregnancy rate as women diagnosed as aLN1-negative [85].…”
Section: Auto-antibodies Specifically Affecting the Reproductive Smentioning
confidence: 99%
See 1 more Smart Citation
“…IL-18 also induces IL-13 and/or IL-4 production by NK cells, mast cells and basophils (51)(52)(53)(54). Human mast cells are known to be a rich source of prostaglandin D 2 , however, the regulation of cyclooxygenase (COX) isoform and prostanoid production by proinflammatory IL-18 cytokine has not been clearly elucidated in HCBDMC (55)(56)(57). Here, we studied the effects of IL-18, anti-IgE, A23187 and the compound 48/80 (an agent containing a cationic region adjacent to a hydrophobic moiety, which works by activating G proteins), on the generation of .prostaglandin D 2 (PGD) and tryptase by HCBDMC.…”
mentioning
confidence: 99%